Archival Approach to IaaS Cloud Services - Stančić, Hrvoje (Array, 2014)
Increasing growth of new technologies and new technological solutions follow increasing demand for new business. The increased usage of new technologies and the higher uses' awareness of the potential problems they bring along have resulted with the need to establish trust in these new services. By services the authors specifically mean Infrastructure-as-a-Service (IaaS) cloud services. The trust can be established in a number of ways such as through the implementation of relevant archival standards, principles of trusted digital repositories, applying to legal procedures, careful service implementation planning etc. In this article the authors focus on the research of the problems and critical points of cloud services, especially paying attention to the areas of governance, compliance, trust, architecture, identity and access management, software isolation, data protection, availability, and incident response.